Manipulating the Interferon Signaling Pathway: Implications for HIV Infection - Nganou-Makamdop, Krystelle; Douek, Daniel C. (Virologica Sinica, 2019)
During human immunodeficiency virus (HIV) infection, type I interferon (IFN-I) signaling induces an antiviral state that includes the production of restriction factors that inhibit virus replication, thereby limiting the infection. As seen in other viral infections, type I IFN can also increase systemic immune activation which, in HIV disease, is one of the strongest predictors of disease progression to acquired immune deficiency syndrome (AIDS) and non-AIDS morbidity and mortality. Moreover, IFN-I is associated with CD4 T cell depletion and attenuation of antigen-specific T cell responses. Therefore, therapeutic manipulation of IFN-I signaling to improve HIV disease outcome is a source of much interest and debate in the field. Recent studies have highlighted the importance of timing (acute vs. chronic infection) and have suggested that specific targeting of type I IFNs and their subtypes may help harness the beneficial roles of the IFN-I system while avoiding its deleterious activities.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Human immunodeficiency virus (HIV); Inflammation; Simian immunodeficiency virus (SIV); Type I interferon (IFN-I)